2001
DOI: 10.2527/2001.79102524x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of boars with a GnRH vaccine (Improvac) eliminates boar taint and increases growth performance.

Abstract: Peri- and postpubertal boars accumulate substances (e.g., androstenone and skatole) in their fatty tissue that are responsible for boar taint in pork. The objective of this study was to assess the efficacy of a GnRH vaccine, Improvac, in eliminating boar taint. Three hundred male (200 intact boars, 100 barrows) crossbred (Large White x Landrace) pigs were used in a 2 x 3 factorially arranged experiment. The respective factors were sex group (barrows, boars treated with placebo, or boars treated with Improvac) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
269
6
37

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(364 citation statements)
references
References 19 publications
52
269
6
37
Order By: Relevance
“…In fact EM and EM1 gained on average less than C (ADG: 254 g/day), but were still more efficient (FCR: 20.26 kg/kg). These findings are in line with recent studies reporting a tendency towards lower ADG for entire males reared in group compared to castrates (Dunshea et al, 2001;D'Souza and Mullan, 2002;Suster et al, 2006). Contrarily, some previous studies reported that entire male pigs had higher ADG and better FCR than castrates (Whittemore et al, 1988;Campbell et al, 1989;Dunshea et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact EM and EM1 gained on average less than C (ADG: 254 g/day), but were still more efficient (FCR: 20.26 kg/kg). These findings are in line with recent studies reporting a tendency towards lower ADG for entire males reared in group compared to castrates (Dunshea et al, 2001;D'Souza and Mullan, 2002;Suster et al, 2006). Contrarily, some previous studies reported that entire male pigs had higher ADG and better FCR than castrates (Whittemore et al, 1988;Campbell et al, 1989;Dunshea et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…However, compared to recent experiments, these studies with entire males of the nineties were carried out with individually penned pigs, which limited the social interactions and, thus, lowered the energy expenditure on activities unrelated to growth. Carcass yield and carcass fat deposition were lower in EM and EM1 than in C, which confirms the results reported by Sather et al (1999), Dunshea et al (2001) and Zeng et al (2002). It is well known that lower backfat deposition rate affects lipid composition of the adipose tissue as the degree of unsaturation of the lipids increases (Bee et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several experiments have been carried out in recent years in order to analyse the advantages of immunocastration by means of Improvac R (Dunshea et al, 2001;Zeng et al, 2002;Cronin et al, 2003;Jaros et al, 2005), or other vaccines ), compared to surgical castration. In all these tests, efficacy of the immunisation was over 97% of the treated pigs and, in most cases, immunised pigs were generally found to have a higher growth rate and better feed efficiency.…”
Section: Immunocastrationmentioning
confidence: 99%
“…In a study comparing early and late immunocastrated pigs with surgical castrates, with a total of 300 animals (Dunshea et al, 2001), pigs treated with Improvac R at 18 and 22 weeks and slaughtered at the age of 26 weeks showed a daily weight gain that -measured over the last 4 weeks prior to slaughter -was 32% higher than the average of surgically castrated animals (slaughtered at the same age). In the case of the 'early treated' group the difference was lower (17%), but in both age groups the feed conversion rate was better than that of surgical castrates.…”
Section: Immunocastrationmentioning
confidence: 99%